2017
DOI: 10.1097/phm.0000000000000601
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Stimulation Based on Chronaxie Increases Fibrosis and Modulates TWEAK/Fn14, TGF-β/Myostatin, and MMP Pathways in Denervated Muscles

Abstract: Electrical stimulation applied to denervated muscles induced muscle fibrosis and atrophy, as well as loss of performance. The TWEAK/Fn14 system, TGF-beta/myostatin pathway, and MMP activity seem to be involved in these deleterious changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Nevertheless, on the 14 th day, whilst D15 improved the neuromuscular performance, increasing SFI, DES15d remained similar to its values observed on the 6 th day (Table ), with a difference between groups ( P = 0.001). Data are also published elsewhere (Pinheiro‐Dardis and Russo; ahead of print).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, on the 14 th day, whilst D15 improved the neuromuscular performance, increasing SFI, DES15d remained similar to its values observed on the 6 th day (Table ), with a difference between groups ( P = 0.001). Data are also published elsewhere (Pinheiro‐Dardis and Russo; ahead of print).…”
Section: Resultsmentioning
confidence: 99%
“…Morphometric analysis was performed according to Pinheiro‐Dardis and Russo . Histological cross‐sections (10 μm) were obtained with a cryostat microtome (Microm HE 505, Jena, Germany), through the middle belly of the TA muscles.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, other preclinical studies have demonstrated no beneficial effects of chronaxie-based ES (frequency: 20 Hz; pulse duration: twice the chronaxie value; 3 s on, 6 s off) on nerve crush-induced muscle fiber atrophy and muscle excitability [11]. In fact, chronaxie-based ES has been reported to induce muscle fibrosis and atrophy in denervated muscles [12]. Furthermore, although high-intensity (16 mA) ES was effective in retarding denervated muscle atrophy, it may have adverse effects on the regeneration of nerve terminals in the neuromuscular junction and/or the membrane systems involved in excitation-contraction coupling [13].…”
Section: Introductionmentioning
confidence: 99%
“…30,31 In the present study, expressions of all mRNA were up-regulated from 3 to 7 d after denervation and maintained to 9 d. Increases in TGF-β1, α-SMA, COL-1α2, and COL-3α1 mRNA in denervated muscle were reported in some studies of gastrocnemius, soleus, and sternocleidomastoid muscles in rodents. [19][20][21][22]32 Palumbo-Zerr et al 33 demonstrated that TGF-β1 induced up-regulation of collagen types 1α1 and 1α2 (encoding types of collagen), which promote fibrosis in human and mouse skin, but the relationship between TGF-β1 and collagen type 1α2 in muscle remains unclear.…”
Section: Effects Of Denervationmentioning
confidence: 99%
“…endomysium, perimysium, and epimysium 16,17 and TGF-β1 have been detected in denervated muscle. 9,[18][19][20][21][22] In addition, connective tissue growth factor, a profibrotic cytokine, is up-regulated by TGF-β1 and induces expression of ECM molecules, such as collagen type 1α2 (COL-1α2). [23][24][25] Hypoxia-inducible factor (HIF)-1α, one of the major proteins expressed under hypoxic state, is increased with physical exercise, 26 hypoxia, 27 and stretching 28…”
Section: Introductionmentioning
confidence: 99%